Transparent Flexible Electrodes Based on Junctionless Copper Nanowire Network via Selective Electroless Metallization of Electrospun Nanofibers. Issue 12 (1st January 2017) - Testa, Andrea; Bernasconi, Roberto; Yoshikawa, Ryohei; Takenaka, Issei; Magagnin, Luca; Shiratori, Seimei
Abstract : A component that is able to transport charges while being transparent to light is fundamental in many devices, including LCD screens, touch panels and solar cells. The most common transparent electrode material is Indium Tin Oxide (ITO) due to its high performance, but the costly production techniques, the rarity of indium and its inherent fragility are pushing the market to look for alternatives. In this work, a facile method for the creation of a junctionless metal nanowire network as transparent electrodes using electrospinning and selective electroless deposition is proposed, without annealing steps or vacuum processes which is needed in conventional nanowire production. The method exploits the insertion of the electroless sensitizing agent into the electrospinning solution for selectively catalyzed metallization of the electrospun nanofiber template without hydrophobic treatments to substrates. The best optoelectronic properties are adequate to replace ITO: Rs = 35 Ω/□ and T = 90% with a very flat transmittance window.